STATISTICAL PARAMETERS OF THE ENERGY CHARACTERISTICS OF BLOCKING ANTICYCLONES - Недострелова, Л. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
Results obtained in the paper rely on the use of classical and modern methods of energetic properties research in weather scale storms on the basis of standard hydrometeorological databases. First of all, it allowed to improve scientific comprehension of dynamic processes which take place during interaction of blocking anticyclone and cyclone. Blocking as a large-scale steady atmospheric process is a main reason of weather anomalies existing at weekly and seasonal time scales. On the other hand, through a comparatively long period of evolution of the blocking anticyclone, the comprehension can allow to improve the medium range and long range weather forecast, especially, forecast of the extreme weather events, related to the process of blocking, such as droughts, heat waves, anticyclone periphery thundershowers etc. It is very interesting to study these processes in view of medium and long-term weather forecasts, atmospheric processes modelling and climate monitoring. There are presently a large number of papers considering climatic features of atmospheric blocking. However, the methodological differences in methods of blocking processes detection, lack of common methods, and differences in the length of studied periods make difficulties for a climatic generalization of blockings. This article aims, on the one hand, to review the existing methods suitable for the recognition of blocking processes and, on the other hand, to offer an approach which uses the dynamic nature of blocking as basis.